Palladium‐Catalyzed Aminosulfonylation of Aryl Iodides by using Na2SO3 as the SO2 Source. Issue 15 (7th April 2014) - Li, Wanfang; Li, Haoquan; Langer, Peter; Beller, Matthias; Wu, Xiao‐Feng
Abstract: We realized an interesting palladium‐catalyzed aminosulfonylation of aryl iodides by using Na2 SO3 as a cheap SO2 source. In most cases, the yields were comparable to those reported by using the 1, 4‐diazabicyclo[2.2.2]octane bis(sulfur dioxide) adduct (DABCO· 2SO2, DABSO) as the SO2 source. Abstract : Gaseous sulfur dioxide is generated ex situ and employed as a cheap sulfonyl source in the palladium‐catalyzed aminosulfonylation of aryl iodides. In most cases, the yields are comparable to those reported by using the 1, 4‐diazabicyclo[2.2.2]octane bis(sulfur dioxide) adduct (DABSO) as the SO2 source.